Settlement pattern of Posidonia oceanica epibionts along a gradient of ocean acidification: an approach with mimics - DONNARUMMA, L.; LOMBARDI, C.; COCITO, S.; GAMBI, M.C. (Hellenic Centre for Marine Research, 2014)
Effects of ocean acidification (OA on the colonization/settlement pattern of the epibiont community of the leaves and rhizomesof the Mediterranean seagrass,Posidoniaoceanica, have been studied at volcanic CO2vents off Ischia (Italy), using “mimics”as artificial substrates. The experiments were conducted in shallowPosidoniastands (2-3 m depth), in three stations on the northand three on the south sides of the study area, distributed along a pH gradient. At each station, 4 rhizome mimics and 6 artificialleaves were collected every three months (Sept 2009-Sept 2010). The epibionts on both leaf and rhizome mimics showed clearchanges along the pH gradient; coralline algae and calcareous invertebrates (bryozoans, serpulid polychaetes and barnacles) weredominant at control stations but progressively disappeared at the most acidified stations. In these extremely low pH sites theassemblage was dominated by filamentous algae and non calcareous taxa such as hydroids and tunicates. Settlement pattern onthe artificial leaves and rhizome mimics over time showed a consistent distribution pattern along the pH gradient and highlightedthe peak of recruitment of the various organisms in different periods according to their life history.Posidoniamimics at theacidified station showed a poor and very simplified assemblage where calcifying epibionts seemed less competitive for space. Thisprofound difference in epiphyte communities in low pH conditions suggests cascading effects on the food web of the meadow and,consequently, on the functioning of the system